Upper Limb Ischemic Gangrene as a Complication of Hemodialysis Access - Shamir O. Cawich; Emil Mohammed; Marlon Mencia; Vijay Naraynsingh (Case Reports in Vascular Medicine)
Upper limb ischemia is a well-recognized complication of dialysis access creation but progression to gangrene is uncommon. We report a case of upper limb ischemic gangrene and discuss the lessons learned during the management of this case. Clinicians must be vigilant for this complication and they should be reminded that it requires urgent management to prevent tissue loss.